Currículo de Arte: continuidades e mudanças para propostas contemporâneas, a partir de uma análise curricular da Educação Artística do período da ditadura civil-militar - Grando, Bruna Cristiane (2019)
The research analyzed the curriculum of Artistic Education, starting from the promulgation of Law no. 5.692/71, as well as comparing it to the 2011’s high school languages, codes and their technologies curriculum of the state of São Paulo, in which the discipline of Art take part of. Freirean conceptions of education and aesthetics were taken as theoretical-methodological reference, as well as the Triangular Approach of Ana Mae Barbosa. The research was conducted from a qualitative research approach, through documents' analysis. The curricula were analyzed by the critical-liberating pedagogical tendency, taking into account the role of education as a means of individuals' emancipation. The study is justified in order to understand the importance of the implantation of Artistic Education in the school curriculum by Law no. 5.692/71and how this introduction could have influenced the curriculum of Art still in the present time, considering that this research understands this area of knowledge as one of the most potent ways to develop creative capacity. The categories of analysis used for curriculum research were epistemological curiosity, sensibility, self-expression, which are imbricated in the main category of creativity. The conclusion is that both curricula have many similarities in the way that they were build, have a technical feature and constitute themselves from the conservative pedagogical tendency, despite differences in methodologies.